Metal Oxide Nanowire Preparation and Their Integration into Chemical Sensing Devices at the SENSOR Lab in Brescia - Angela Bertuna; Guido Faglia; Matteo Ferroni; Navpreet Kaur; Hashitha M. M. Munasinghe Arachchige; Giorgio Sberveglieri; Elisabetta Comini (Sensors, 2017)
Metal oxide 1D nanowires are probably the most promising structures to develop cheap stable and selective chemical sensors. The purpose of this contribution is to review almost two-decades of research activity at the Sensor Lab Brescia on their preparation during by vapor solid (n-type In2O3, ZnO), vapor liquid solid (n-type SnO2 and p-type NiO) and thermal evaporation and oxidation (n-type ZnO, WO3 and p-type CuO) methods. For each material we’ve assessed the chemical sensing performance in relation to the preparation conditions and established a rank in the detection of environmental and industrial pollutants: SnO2 nanowires were effective in DMMP detection, ZnO nanowires in NO2, acetone and ethanol detection, WO3 for ammonia and CuO for ozone.